ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL FUNGSI - Kurniawan, Ade; Juliangkary, Eliska; Pratama, Martoni Yuda; Saputra, Irwadi (Media Pendidikan Matematika, 2019)
This study aims to describe the difficulties experienced by students in solving functional problems. This type of research is descriptive qualitative. The research respondents were students of class X. Data collection techniques in this study with test and interview methods were followed by 28 students. The researcher took 6 students to be interviewed, 5 of them women and 1 male. Based on the results of the tests and interviews, it can be concluded that the difficulties experienced by students in completing the function questions, namely students have difficulty in applying the principle besides that students do not write down what is known and asked according to the request. Students' difficulties in transferring knowledge are difficulties in understanding the concepts of functions and basic concepts of integers. Students have not mastered the function material so that they do not understand the questions given and are less skilled in working on the questions given. Another difficulty is that the procedure carried out by students deviates in certain steps. The difficulties experienced by students in the calculation are that students are less careful in addition, subtraction, multiplication, and division operations in operations.